(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
A patient with suspected ectopic pregnancy was managed successfully with expectant approach using serial serum ²hCG monitoring. Expectant management can be a useful form of treatment for ectopic pregnancy in selected patients. DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12476 J Bangladesh Coll Phys Surg 2012; 30: 170-172